Influence of thermal annealing on the properties of evaporated Er-doped SnO2 - Machado, Diego H.O. [UNESP]; da Silva, José H.D. [UNESP]; Tabata, Américo [UNESP]; Scalvi, Luis V.A. [UNESP] (Elsevier, 2019)
Er-doped tin dioxide thin films, deposited on glass substrates by a combination of sol-gel and resistive evaporation techniques, are investigated. The sol-gel route is used for powder preparation, which serves as material source for resistively evaporated thin films. The annealing temperature influences the Er3+ location, that reflects on the photoluminescence (PL) related to 2H11/2→4I15/2 and 4S3/2→4I15/2 Er3+ transitions. The lower annealing temperature, 300 °C, leads to PL emission, which vanishes for higher annealing temperatures. Annealing temperature above 300 °C enlarges the crystallites and allows diffusion of Er ions into the sample, increasing the population of substituted Sn sites. Then, the population of grain boundary located luminescent sites is decreased, leading to higher conductivity concomitant with absence of PL signal. Evaporated SnO2 films have the advantage of a stable electrical signal and the deposition on hydrophobic surfaces. Emission of evaporated SnO2 on GaAs substrates is also shown, yielding the substrate influence.
Keywords: Erbium; Resistive evaporation; Sol-gel; Thin films; Tin dioxide